Seasonal Variability and Drivers of Microzooplankton Grazing and Phytoplankton Growth in a Subtropical Estuary - Anderson, Sean R.; Harvey, Elizabeth L. (Frontiers in Marine Science, 2019)
Rates of microzooplankton grazing and phytoplankton growth are seldom measured with respect to time, yet such estimates may better reflect temporal variability in coastal phytoplankton communities and offer insight into mechanisms that control populations. To assess seasonal patterns in rates, we performed 41, weekly dilution experiments over a full year in the Skidaway River Estuary (GA), measuring rates of phytoplankton growth, microzooplankton grazing, and viral lysis based on total chlorophyll and group-specific abundances (Synechococcus spp., picoeukaryotes, and nanoeukaryotes). Seasonal variability in microzooplankton grazing (0-2.11 d-1) and phytoplankton growth rates (0-2.43 d-1) was observed, with highest values typically recorded in summer and lowest in winter. Grazing pressure was strongest in winter-spring, as phytoplankton accumulation rates were often negative (-0.16-0.28 d-1). Rates varied similarly over seasons for chlorophyll, pico-, and nanoeukaryotes, while rates on Synechococcus spp. were rarely significant in dilutions and did not follow seasonal trends. Few experiments (7%) yielded significant rates of viral lysis. Temperature correlated most strongly with phytoplankton growth rates (R2 = 0.46-0.56), but not grazing rates (R2 = 0.11-0.27), which were more likely driven by observed seasonal shifts in plankton community composition (e.g. fall diatom blooms). Establishing temporal rate measurements is critical to identify factors that drive phytoplankton growth and mortality and accurately predict shifts in phytoplankton population dynamics and food web processes within marine systems.